2003
DOI: 10.3310/hta7270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating non-randomised intervention studies

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
1,464
0
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,140 publications
(1,533 citation statements)
references
References 306 publications
(248 reference statements)
18
1,464
0
18
Order By: Relevance
“…using the wrong statistical model). 6,7,93,[106][107][108] Consequently, relying on evidence from observational studies about the effects of treatment on common outcomes -rather than considering it to be "hypothesisgenerating" -may well have adverse consequences for patients and public health.…”
Section: Biases Due To Differences In Underlying Risks Of Health Outcmentioning
confidence: 99%
See 2 more Smart Citations
“…using the wrong statistical model). 6,7,93,[106][107][108] Consequently, relying on evidence from observational studies about the effects of treatment on common outcomes -rather than considering it to be "hypothesisgenerating" -may well have adverse consequences for patients and public health.…”
Section: Biases Due To Differences In Underlying Risks Of Health Outcmentioning
confidence: 99%
“…106 It has been concluded that these reviews identified many examples where the results of the same intervention were on average the same, but also many examples where the results differed. For example, there have been many claims about the benefits of various vitamin supplements based on observational studies 128,129 that have been reliably refuted by large-scale randomized trials.…”
Section: Biases Due To Differences In Underlying Risks Of Health Outcmentioning
confidence: 99%
See 1 more Smart Citation
“…The RCT is widely regarded as the design of choice when assessing the effectiveness of health care interventions 168 and we acknowledge the controversy over the inclusion of non-randomised evidence. Non-randomised studies were included in the search because some treatment approaches may not have been evaluated by RCTs, and also to increase the precision of the findings for interventions evaluated by a limited number of studies.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…[14] (see Table 1). Overall scores were not computed due to concerns over their interpretability [14], but the impact of poorly endorsed validity criteria was examined in moderator analysis.…”
Section: Study Validity Criteriamentioning
confidence: 99%